Tribological behavior of environmentally friendly borate ionic liquids with low corrosion degree. (October 2021) - Yue, Shuang; Gao, Xing; Lu, Guowang; Zang, Shuliang; Deng, Guichun; Wang, Feiming
Abstract: Two novel halogen-free liquids additives [DHB][BScB] and [MA-BIm][BScB] are synthesized and their tribological performance in 500 N base oil are evaluated using 4-ball machine for the first time. The results show that [DHB][BScB] and [MA-BIm][BScB] can decrease the friction coefficient of 500 N base oil by 42.7% and 42.1% at 2.5 wt% concentration respectively and they both possess excellent corrosion resistance. According to the analysis results of X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM), [DHB][BScB] and [MA-BIm][BScB] can form chemical films consisting of iron oxide and B2 O3 on the worn steel surface. In addition, a lubrication mechanism is speculated and there may be a competitive adsorption between anion and cation. Graphical Abstract: ga1 Highlights: Two kinds of novel halogen-free and environmentally friendly borate ionic liquids are synthesized. Two borate ionic liquids can effectively enhance the tribological properties of 500 N base oil. The thermal stabilities of two ionic liquids are evaluated and they both possess higher decomposed temperature. Two kinds of environmentally friendly ionic liquids exhibit excellent anti-corrosion properties. A lubrication mechanism is speculated that there may be a competitive adsorption between anion and cation.